Portaria PRES nº 88, de 14 de abril de 2021 - Edmar Gomes Machado (DMPF-e, Brasília, DF, 16 abr. 2021. Caderno Administrativo, p. 46., 2021)
Altera o caput do art. 1º da Portaria PRES nº 72, de 16 de março de 2021.